An ecology of space. Architectural design for transboundary relationships - Hisham El-Hitami; Mona Mahall; Asli Serbest (Agathón)
While architectural discussions on ecology focus on technical considerations, a deeper understanding of the notion and its aspects of the inter-relationality between things and beings presents a broader perspective. Ecological architecture could play a central role in shaping the relationships that human beings have with their environment. By identifying the façade as the focal point for cross-border relationships linking interior and exterior spaces, an analysis of historical and contemporary architecture shows how architects have designed transitional spaces to promote these relationships. Such ambiguous spaces are exemplarily found in historic box-type windows, initially intended for thermal insulation. Even these little transitional spaces bear the potential of mediating between inside and out. In this sense, architecture might assume a central ecological role in shaping the relationships humans entertain with their environments.